French-English agricultural dictionary - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
French-English agricultural dictionary : with English-French index compiled by D O'D Bourke ISBN 0 85198 7672 Hbk UKL29.50 CAB International, Wallingford Oxon OX10 ODE, UK